2021
DOI: 10.1590/1516-3180.2020.0616.r3.1902021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of xerostomia and its association with systemic diseases and medications in the elderly: a cross-sectional study

Abstract: Saliva plays an important role in oral health. Besides being involved in protection against bacteria and fungi, it transports nutrients and digestive enzymes, lubricates the mucosa, facilitates mastication, swallowing and speech, and acts in the process of tooth remineralization. 1,2 Saliva is produced by salivary glands, which are exocrine, such as the parotid, submandibular and sublingual glands. These are the most important pairs of glands and are responsible for 95% of saliva production. 3 In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(54 reference statements)
2
10
0
Order By: Relevance
“…Lesions in the hard and soft tissues of the mouth, which many patients report as causing discomfort and pain, are common in patients with xerostomia, due to dryness on the surface of the tongue, palate, oral floor, and mucosa 15,21,27 . The xerostomia scores in this study were high, consistent with other studies 13,19,24,[28][29][30][31] . In the present study, 45.5% of the elderly have depression or anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Lesions in the hard and soft tissues of the mouth, which many patients report as causing discomfort and pain, are common in patients with xerostomia, due to dryness on the surface of the tongue, palate, oral floor, and mucosa 15,21,27 . The xerostomia scores in this study were high, consistent with other studies 13,19,24,[28][29][30][31] . In the present study, 45.5% of the elderly have depression or anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Although proton-pump inhibitors do not possess anticholinergic activity, they may activate a similar H/K ATPase in the salivary gland or reduce water brash leading to less vagal reflux for saliva production. This was supported by Fornari et al 26 who found elderly people using continuous medication for the gastrointestinal tract were more likely to have xerostomia.…”
Section: Discussionmentioning
confidence: 65%
“…Xerostomia has high incidence with age, which was demonstrated by the reports from the literature that one in ten for younger and one in four for elder Australians (55 years old as cutoff) experienced dry mouth, with a prevalence of 9.3% among 15to 34-year-olds, 11% among 35-to 54-year-olds, 17.6% among 55-to 74-year-olds, and 26.5% among those older than 75 years old (Jamieson and Thomson, 2020). Another study also reported xerostomia was one in five (19.1%) by 293 elderly people older than 60 years in Vanini, Brazil (Fornari et al, 2021). Moreover, xerostomia affects more than one-third of postmenopausal women (Nederfors, 2000).…”
Section: Discussionmentioning
confidence: 93%